Dendritic defect-rich palladium–copper–cobalt nanoalloys as robust multifunctional non-platinum electrocatalysts for fuel cells - Chaozhong Li (Nature Portfolio, 2018)
Fuel cells are promising for sustainable energy generation, but are limited by the performance of electrocatalysts. Here the authors synthesize dendritic palladium–copper–cobalt nanoalloys with electrocatalytic activity for oxygen reduction and formic acid oxidation as well as alcohol tolerance.